Exploring The Application of The Radec Learning Model (Read-Answer-Discuss-Explain and Create) in Improving Collaboration Skills of Low-Able Mathematics Students: A Case Study - Fitri, Tri Mentari; Caswita, Caswita (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
Collaboration in learning mathematics is very important, in everyday learning the teacher does not settle for collaborative learning. At SMA TRI SUKSES itself the learning process is still only focused on the critical thinking skills of each individual student. So that the attractiveness of the students' mathematical abilities is still very visible. This study explores how a teacher implements learning interventions in the classroom and sees how students' abilities develop and looks at students' responses to applied learning. In this study I explored high school students in class XI SMA TRI SUKSES Lampung. - 34 male and female students, determined 4 students with the lowest mathematical ability to be observed and involved a teacher in the observation Using the RADEC learning model. Data collection was carried out through interviews, reflection on the teacher's journal, classroom observations, and learning observations by collecting data qualitatively using a purposive sampling technique in two trials. From the observation results, the application of the RADEC model was quite capable of helping students improve their collaborative skills, initially these low-ability students could only be silent and bowed during the collaboration process in learning, after the model was applied in a fun way and good motivation from the teacher and a group of students with low mathematical abilities seemed to have developed in their collaborative skills so that it affected students' mathematical and cognitive ability scores, which were originally an average of 76.75 and 79.5 to 80.25 and 82.5.Kolaborasi dalam pembelajaran matematika sangatlah penting, dalam pembelajaran sehari-hari guru tidak terpaku pada pembelajaran kolaboratif. Di SMA TRI SUKSES sendiri proses pembelajaran masih hanya terfokus pada kemampuan berpikir kritis setiap individu siswa. Sehingga daya tarik kemampuan matematika siswa masih sangat terlihat. Penelitian ini mengeksplorasi bagaimana seorang guru melaksanakan intervensi pembelajaran di kelas dan melihat bagaimana kemampuan siswa berkembang serta melihat respon siswa terhadap pembelajaran yang diterapkan. Dalam penelitian ini saya mengeksplorasi siswa SMA kelas XI SMA TRI SUKSES Lampung. - Siswa laki-laki dan perempuan sebanyak 34 orang, ditentukan 4 orang siswa yang kemampuan matematikanya paling rendah untuk diamati dan dilibatkan seorang guru dalam observasi tersebut. Menggunakan model pembelajaran RADEC. Pengumpulan data dilakukan melalui wawancara, refleksi jurnal guru, observasi kelas, dan observasi pembelajaran dengan pengumpulan data secara kualitatif menggunakan teknik purposive sampling dalam dua kali uji coba. Dari hasil observasi penerapan model RADEC cukup mampu membantu siswa dalam meningkatkan kemampuan kolaboratifnya, awalnya siswa berkemampuan rendah ini hanya bisa diam dan tertunduk pada saat proses kolaborasi dalam pembelajaran, setelah model diterapkan dengan cara yang menyenangkan dan motivasi yang baik dari guru dan kelompok siswa yang kemampuan matematikanya rendah nampaknya telah berkembang dalam kemampuan kolaboratifnya sehingga mempengaruhi skor kemampuan matematika dan kognitif siswa yang semula rata-rata 76,75 dan 79,5 menjadi 80,25 dan 82,5.